A teoria simulacionista da memória é sobre simulação? - Andonovski, Nikola (Voluntas: Revista Internacional de Filosofia, 2019)
This essay investigates the notion of simulation and the role it plays in Kourken Michaelian’s simulation theory of memory. I argue that the notion is importantly ambiguous and that this ambiguity may threaten some of the central commitments of the theory. To illustrate that, I examine two different conceptions of simulation: a narrow one (simulation as replication) and a broad one (simulation as computational modeling), arguing that the preferred narrow conception is incompatible with the claim that remembering involves the simulation of past episodes. Investigating possible solutions, I suggest that, despite some relatively serious consequences, the theory may be better off subscribing to the broad notion of simulation.